Application of financial modeling for mining companies - K. K. Murakova (Путеводитель предпринимателя, 2020)
The article reflects some methodological and practical aspects of the study of the possibilities offinancial modeling. The simplest financial model is based on the example of a mining company. The pros and cons ofthe use ofmodelingforforecasting the development of the organization are shown.